STRUGGLE FOR THE GRAVEYARDS - BIZARRENESS OF THE PROPAGANDAS IN MACEDONIA (Annual of the Faculty of Philosophy in Skopje, 2011)
The purpose of this article is a segment of the propaganda 's wars in Macedonia at the end of the XIX and the beginning of the XX century. During this period Macedonia was an arena of propaganda 's activities and confrontations among Greek, Serbian, Bulgarian and Romanian propagandas. In order to take more adherents the mentioned propagandas did not hesitate to take various means and methods. During theirs activities they abused, on most vulgar way, the basic needs of the Macedonian orthodox population in order to impose their national consciousness. In the propaganda's war for the "soul of the living" even the dead soul had not been spared. Thus a bizarre struggle for the graveyards and dead souls started. Such struggle is not understandable for Christian 's moral and ethics and for the human sense in general.
Keywords: MACEDONIA; PROPAGANDA; GRAVEYARDS